2006
DOI: 10.2343/geochemj.40.265
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal source rocks of the Meng'entaolegai Ag-Pb-Zn deposit in the granite batholith, Inner Mongolia, China: Constrained by isotopic geochemistry

Abstract: The Meng'entaolegai Ag-Pb-Zn-In polymetallic deposit is located in the eastern part of Inner Mongolia. It consists of a hydrothermal quartz-sulfide vein deposit hosted within a Hercynian granite massif which is about 400 km 2 in size. More than 40 orebodies are found in the orefield which is 6 km in length from east to west and 200 to 1,000 m in width from south to north. All orebodies are controlled by E-W trending faults. Economic resources are dominated by Pb and Zn (reserves of Pb and Zn are 0.17 Mt and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Rare earth element (REE) geochemistry studies can also provide information regarding the sources of ore‐forming materials (Zhao and Jiang, ). Likewise, sulphur and strontium isotopes can be used to trace the sources of S, Ca, Sr, and Ba in metallogenic systems effectively (Ruiz and Kesler, ; Barbieri and Bellanca, ; Hoefs, ; Jiang et al , ; Chen et al , , ; Zhu et al , ; Li et al , ; Wang et al , ; ). Nevertheless, the use of only single‐isotope data may yield incomplete conclusions, and it may even result in contradictory conclusions (Dejonghe et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth element (REE) geochemistry studies can also provide information regarding the sources of ore‐forming materials (Zhao and Jiang, ). Likewise, sulphur and strontium isotopes can be used to trace the sources of S, Ca, Sr, and Ba in metallogenic systems effectively (Ruiz and Kesler, ; Barbieri and Bellanca, ; Hoefs, ; Jiang et al , ; Chen et al , , ; Zhu et al , ; Li et al , ; Wang et al , ; ). Nevertheless, the use of only single‐isotope data may yield incomplete conclusions, and it may even result in contradictory conclusions (Dejonghe et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Geochronological data published for the Mo (Pb-Zn-Ag) mineralization in the southern part of the Great Xing'an Range [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]…”
Section: Ages Of Magmatism and Metallogenesismentioning
confidence: 99%
“…Geochronological data published for the Mo (Pb-Zn-Ag) mineralization in the southern part of the Great Xing'an Range [55,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] are shown that this region records four stages for Mo (Pb-Zn-Ag) mineralization: (1) Late Permian (265 Ma), (2) Middle Triassic (244-235 Ma), (3) Middle-Late Jurassic (179-161 Ma), and (4) Late Jurassic-Early Cretaceous (147-132 Ma). The age of 162.6 ± 1.5 Ma obtained in this study is also consistent with the Middle-Late Jurassic stage of Mo-polymetallic mineralization in the southern part of the Great Xing'an Range, such as the Lianhuashan Cu + Ag + Mo deposit with a zircon U-Pb age of 161.8 Ma and the Shuangjianzishan deposit with a pyrite Re-Os isochron age of 165 ± 4 Ma, and slightly younger than the Meng'enTolgoi deposit, which had a muscovite Ar-Ar isochron age of 179 ± 2 Ma [58][59][60] (Figure 17). in this study is also consistent with the Middle-Late Jurassic stage of Mo-polymetallic mineralization in the southern part of the Great Xing'an Range, such as the Lianhuashan Cu + Ag + Mo deposit with a zircon U-Pb age of 161.8 Ma and the Shuangjianzishan deposit with a pyrite Re-Os isochron age of 165 ± 4 Ma, and slightly younger than the Meng'enTolgoi deposit, which had a muscovite Ar-Ar isochron age of 179 ± 2 Ma ( Figure 17) [57,58].…”
Section: Ages Of Magmatism and Metallogenesismentioning
confidence: 99%
“…According to Zhu et al (2004Zhu et al ( , 2006, the Meng'entaolegai deposit is a magmatic hydrothermal deposit genetically connected with Early Yanshanian magmatic activities.…”
Section: Dulong Sn-zn Depositmentioning
confidence: 99%